2007
DOI: 10.1002/adma.200701052
|View full text |Cite
|
Sign up to set email alerts
|

Rubrene/Fullerene Heterostructures with a Half‐Gap Electroluminescence Threshold and Large Photovoltage

Abstract: Tremendous interest in organic semiconductors for the development of light-weight and flexible electronic devices has been generated, owing to their ease of fabrication and suitability to large-area applications. [1][2][3][4][5] However, there are still many unexplored possibilities offered by these conjugated materials. [6,7] We demonstrate here a new structure that permits efficient integration of both light-and current-generation functions from a rubrene/fullerene heterostructure into an efficient organic d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
95
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 116 publications
(102 citation statements)
references
References 32 publications
5
95
2
Order By: Relevance
“…[17][18][19][20][21] This process is referred to as Auger recombination. Auger recombination is a common electronic process in inorganic semiconductors 40 and quantum dots, in particular when the carrier concentration is high.…”
Section: Auger Recombinationmentioning
confidence: 99%
See 1 more Smart Citation
“…[17][18][19][20][21] This process is referred to as Auger recombination. Auger recombination is a common electronic process in inorganic semiconductors 40 and quantum dots, in particular when the carrier concentration is high.…”
Section: Auger Recombinationmentioning
confidence: 99%
“…This type of OLED has operating voltages well below the HOMO-LUMO energy gaps of the emitter molecules; i.e., the output photon energies are higher than the input electrical energies. [17][18][19][20][21] In this report, we provide a review on the electronic processes at organic heterojunctions and Auger-electron-stimulated ultralow-voltage OLEDs.…”
Section: Introductionmentioning
confidence: 99%
“…Pandey et al reported a similar device using a combination of rubrene and fullerene. 3 Their device showed maximum luminance of ca. .…”
Section: Ipce (%)mentioning
confidence: 99%
“…Recently, organic optoelectronic devices, such as, organic lightemitting diodes (OLEDs), 1 organic photovoltaic device (OPVs), 2,3 organic photodiodes (OPDs), [4][5][6][7] and organic phototransistor 8 have been actively studied. Because a certain organic material has a characteristic optical property, a new functional device is expected, for example, that has both light-emitting and photo-sensing abilities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation